Antibacterial Properties Of Ocimum Spp. (ocimum Basilicum L. And Ocimum Basilicum Var. Purpurascens) Against Selected Bacteria - Nurul Nadia Salleh; Norlelawati Ariffin; Hanis Nadia Yahya; Hafiza Yahya (East African Scholars Publisher, 2024)
Volume:4 Issue:10 (page:194-200)